Colistin plus meropenem combination is synergistic in vitro against extensively drug-resistant Pseudomonas aeruginosa, including high-risk clones. (September 2019) - Montero, María M.; Domene Ochoa, Sandra; López-Causapé, Carla; VanScoy, Brian; Luque, Sonia; Sorlí, Luisa; Campillo, Núria; Padilla, Eduardo; Prim, Núria; Segura, Concepción; Pomar, Virginia; Rivera, Alba; et al.
Highlights: Extensively drug resistant (XDR) Pseudomonas aeruginosa causes severe infections. There is a high risk of resistance selection in these clones. Colistin has been the only available treatment but that is not an optimal treatment. Combination regimens could suppress emerging resistance. Colistin plus meropenem is synergistic in vitro against XDR Pseudomona aeruginosa . Abstract: Background: Extensively drug-resistant (XDR) Pseudomonas aeruginosa ( P. aeruginosa ) and particularly P. aeruginosa high-risk clones, are of growing concern because treatment options are limited. For years, colistin monotherapy has been the only available treatment, but is well known that is not an optimal treatment. A combination of colistin with another antibiotic could be a possible therapeutic option. Objectives: This study aimed to investigate effective antibiotic combinations against 20 XDR P. aeruginosa isolates obtained in a Spanish multicentre study (2015). Methods: Forty-five checkerboards with six antipseudomonal antibiotics (amikacin, aztreonam, ceftazidime, meropenem, colistin, and ceftolozane/tazobactam) were performed to determine whether combinations were synergic or additive by fractional inhibitory concentration indices. On average, 15 different regimens were evaluated in duplicate against the three most prevalent high-risk clones (ST175, ST235, ST111) by time-kill analyses over 24 h. The combination showing synergism in the three high-risk clones was validated in all studied XDR isolates. Results: In time-kill curves, the untreated control failed, as did each study regimen when administered alone. Two combinations were synergistic in the three high-risk clones that were initially studied: amikacin plus ceftazidime and colistin plus meropenem, with the second being the most effective combination. The efficacy of colistin plus meropenem was then tested in all 20 isolates. A synergistic bacterial density reduction for the duration of the study occurred in 80% of the entire XDR collection. Conclusions: These data suggest that colistin plus meropenem may be a useful combination for the treatment of infections due to XDR P. aeruginosa, including high-risk clones, which warrants evaluation in a clinical trial.